Impact of water erosion on the profitability of agricultural producers in the partido of Tres Arroyos, Pampean Austral Region, Argentina - Sequeira, Nahuel David; Vazquez, Patricia (Revista Geográfica de América Central., 2021)
Worldwide, water erosion is one of the most relevant soil degradation processes. The objectives of the present work are: a) to estimate the current and potential water erosion rate, and the variation of the total loss of agricultural soils in the partido (roughly translated as district) of Tres Arroyos (Pampean Austral Region) in the province of Buenos Aires, Argentina, for the 1989/90, 2002/03, and 2019/20 agro-productive campaigns; and b) to develop an approach to estimating the economic loss due to the decrease in soil productivity caused by water erosion in the study area. Methodologically, the rate of erosion and rate of soil loss and their temporal evolution were calculated, and the decrease in yield of three main crops and their economic impact was determined. Since 2002/03, the partido (district) shows a decrease in productivity, due to the increase in the area of cultivated land and the existence of erosive processes, translating into economic damage to producers, and highlighting the urgency to develop strategies focused on a more sustainable production model.